Calwater2 scanning flow CCN measurements at Bodega Bay Marine Laboratory - Kreidenweis, Sonia M.; Atwood, Samuel A.; DeMott, Paul J. (Colorado State University. Libraries, 2015)
Scanning flow CCN measurements were conducted at the Bodega Bay Marine Laboratory (BML) as part of the Calwater2 campaign.
All valid data from the study is included in the "data" directory. Metadata with descriptions of file format is included in the "Metadata.txt" file. A README file provides an overview of these measurements, the Calwater2 study, and the calibration and use of this dataset.
Department of Atmospheric Science